Research on the Development and Operation Model of Yunnan De'ang Sour Tea Featured E-commerce Information Platform - Wen, Xinyun; Yang, Jianfei (International Journal of Agriculture and Food Sciences Research, 2024)
This study aims to provide empirical research on the application of rural e-commerce in rural revitalization through in-depth analysis of the De'ang sour tea industry, and explore how to effectively protect and inherit intangible cultural heritage through e-commerce platforms and digital technology, while promoting the comprehensive development of rural economy and society. Through this study, we aim to provide strategic recommendations for the protection, inheritance, and market development of De'ang sour tea production techniques, and contribute wisdom and strength to the implementation of rural revitalization strategies.